Extraction And Antimicrobial Properties Of Polysaccharide From Pleurotus Eryngii - Aina Samsudin,; Nurul Ain Amanina Dzulkifli,; Mohamad Azani Abd Khadir Jalani,; Srivani Sellathoroe,; Rahayu Ahmad (Universiti Sains Islam Malaysia, 2024)
Junior Researcher International Conference (iJURECON) Kolej Genius Insan (KGI) 17 dan 18 November 2020 Pages : 249-253